Finance and Development, March 1971. (Finance and Development; Finance and Development, 1971)
This paper describes modernization of ports in Peru. With the sea so predominant in the life of the country, modern ports are vital in Peru. A program has been undertaken to abandon the numerous obsolete ports served by barges and to establish a few strategically situated ports-modern, mechanized, and with terminals having direct mooring facilities. At the same time, Callao, the country's chief port, has been improved, and specially equipped ports are being planned for fishing products.